2013
DOI: 10.1080/10934529.2013.781875
|View full text |Cite
|
Sign up to set email alerts
|

The cytological effects of HBCDs on human hepatocyte L02 and the potential molecular mechanism

Abstract: The concentration of hexabromocyclododecanes (HBCDs) in the environment media and organism samples are gradually rising with the increase of HBCDs usage. This study is designed to investigate the cytological effects of HBCDs on human hepatocyte L02 and explore the potential molecular mechanism. The results of CCK-8 assay showed that high concentration of HBCDs (>20 μM) significantly suppressed cell survival, while comparatively lower dose of HBCDs (10(-13)-10(-7)M) slightly stimulated cell proliferation (P < 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 30 publications
2
12
0
Order By: Relevance
“…Furthermore, in the immortalised human hepatocyte L02 cell line, the EC 50 for a 24-hour exposure to HBCD was reported as ca. 60 μM (An et al 2013). Hence, the EC 50 value for this hepatic cell line treated with HBCD is consistent with previously published values, for the case of exposures conducted in the presence of serum which more closely reflects the in vivo situation.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Furthermore, in the immortalised human hepatocyte L02 cell line, the EC 50 for a 24-hour exposure to HBCD was reported as ca. 60 μM (An et al 2013). Hence, the EC 50 value for this hepatic cell line treated with HBCD is consistent with previously published values, for the case of exposures conducted in the presence of serum which more closely reflects the in vivo situation.…”
Section: Discussionsupporting
confidence: 91%
“…In several in vitro studies, induction of cell apoptosis by exposure to high concentrations of HBCD in HepG2 cells (Hu et al 2009;An et al 2014) and human L02 hepatocytes (An et al 2013) has been suggested to result from increased production of reactive oxygen species (ROS). However, a slight increase in ROS has also been observed after low concentration (10 −7 −10 −1 μM) exposures in human L02 hepatocytes, while there was no acute toxic effect reported (An et al 2013;Zou et al 2013). More studies are necessary to better understand whether any molecular changes result from concentrations that are realistic for human exposure.…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
“…The ROS level in HBCDD treated cells was elevated in a time‐dependent manner. It was also shown that the ROS level induced by low concentrations of HBCDDs was comparatively lower than that induced by high concentrations of HBCDDs (An et al., 2013).…”
Section: Assessmentmentioning
confidence: 99%
“…In vitro steroidogenic effects of mixtures of persistent organic pollutants (POPs) extracted from burbot (Lota lota) caught in two Norwegian lakes.HBCDDs were not tested alone but in chemical mixture.An et al. (2013). The cytological effects of HBCDs on human hepatocyte L02 and the potential molecular mechanism.High concentration of HBCDDs (> 20 μM) decreased survival of L02 hepatocytes, lower dose of HBCDDs (10 −13 –10 −7 M) stimulated cell proliferation and up‐regulation of PCNA protein expression level.An et al.…”
Section: Appendix D – Mode Of Action Studiesmentioning
confidence: 99%
“…Comet assay DNA single-strand breaks (SSB) were evaluated with the alkaline single-cell gel electrophoresis [22]. Briefly, normal melting point agarose (NMA, 1 %) was prepared on the frosted microscope slides.…”
Section: Cell Viabilitymentioning
confidence: 99%